Comparative Clinical Study of Nasya and Jala Neti in Allergic Rhinitis (AYUSHDHARA, 2021)
Allergic rhinitis is a type of inflammation associated with a group of symptoms affecting the nose. When a person with allergic rhinitis breathes in an allergen such as pollen, animal dander, mold, or dust, the body releases chemicals that cause allergy symptoms. Now-a-days, it is a common inflammation in the population. Nasya is very commonly performed in Ayurveda for the same. In the present study another procedure “Jalaneti '' is also selected, which is a classical procedure of Yoga Therapy. The present study has been done to compare the effect of nasya and jalaneti in allegic rhinitis. The study was conducted at Panchkarma Department of Shree Saptashrungi Ayurved Mahavidyala and Hospital, panchvati, Nashik, Maharashtra. Total number of 20 patients of age 10-70 years having allegic rhinitis or Jirnapratishyay as mentioned in Ayurvedic classics were selected. Out of which Nasya with Vacha Tail was given to 10 patients and Jalaneti with Saindhav Jala was given to another 10 patients. Comparison was done by subjective assessment. It was observed that Nasya done as per the textual methods is highly effective in Allergic Rhinitis and showing a way out to the individual suffering from chronic disease. The study confirmed the effect of Nasya in Allergic Rhinitis in improving the quality of life of patients without any untoward effects.